Chaos in Electronic Drive Systems - Chau, K. T. (IEEE Wiley, 2012)
In Chaos in Electric Drive Systems: Analysis, Control and Application authors Chau and Wang systematically introduce an emerging technology of electrical engineering that bridges abstract chaos theory and practical electric drives.